A Validation Study of Cultural Awareness Related Mathematics for Primary School Using Rasch Model - Iranti, Agna Dewi; Putra, Zetra Hainul; Alim, Jesi Alexander (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2024)
This study aims to develop and test the feasibility of students' cultural awareness items. The method used in this study is quantitative. A total of 24 items were developed to measure cultural awareness, and the research subjects consisted of 23 students. Data analysis was carried out using the Rasch model. The results showed that of the 24 items developed, 20 items were declared feasible to use, with each person and item reliability showing relatively high values. However, some items still need to be improved to improve their ability to measure more diverse students' cultural awareness.